2003
DOI: 10.1096/fj.03-0086com
|View full text |Cite
|
Sign up to set email alerts
|

Isolevuglandins, a novel class of isoprostenoid derivatives, function as integrated sensors of oxidant stress and are generated by myeloperoxidase in vivo

Abstract: Isolevuglandins (isoLGs) are a family of reactive gamma-ketoaldehydes generated by free radical oxidation of arachidonate-containing lipids through the isoprostane pathway. Elevated plasma levels of isoLG protein adducts are observed in subjects with atherosclerosis compared with age/gender-matched controls. However, mechanisms for the generation of isoLGs in vivo are not established. Here we show that free radical-induced peroxidation promoted by the myeloperoxidase (MPO)/H2O2 system of leukocytes serves as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 69 publications
1
52
0
3
Order By: Relevance
“…Berliner and colleagues (20)(21)(22)(23)(24)(25)(26) reported that mildly oxidized LDL, which was still recognized by the LDL receptor, stimulated human aortic endothelial cells to bind monocytes but not neutrophils and caused artery wall cells to produce the potent monocyte chemoattractant monocyte chemoattractant protein-1 and the differentiation factor monocyte colony stimulating factory. Subsequently, it was found that the biological activity of this minimally modified LDL (MM-LDL) was attributable to the oxidation of LDL phospholipids, which contain arachidonic acid in the sn -2 position (27)(28)(29)(30)(31)(32)(33)(34). Direct measurement of these oxidized phospholipids in atherosclerotic lesions in animals suggested that they exist at concentrations that would be biologically active in vivo (29).…”
Section: What Causes Monocytes To Enter the Artery Wall In The First mentioning
confidence: 99%
See 2 more Smart Citations
“…Berliner and colleagues (20)(21)(22)(23)(24)(25)(26) reported that mildly oxidized LDL, which was still recognized by the LDL receptor, stimulated human aortic endothelial cells to bind monocytes but not neutrophils and caused artery wall cells to produce the potent monocyte chemoattractant monocyte chemoattractant protein-1 and the differentiation factor monocyte colony stimulating factory. Subsequently, it was found that the biological activity of this minimally modified LDL (MM-LDL) was attributable to the oxidation of LDL phospholipids, which contain arachidonic acid in the sn -2 position (27)(28)(29)(30)(31)(32)(33)(34). Direct measurement of these oxidized phospholipids in atherosclerotic lesions in animals suggested that they exist at concentrations that would be biologically active in vivo (29).…”
Section: What Causes Monocytes To Enter the Artery Wall In The First mentioning
confidence: 99%
“…Myeloperoxidase reaction products have been found in human atherosclerotic lesions (52), and there is increasing evidence that the myeloperoxidase pathway can generate proinflammatory oxidized lipids (32,(53)(54)(55)(56)(57)(58)). Another pathway that may be a potential source of reactive oxygen species for the generation of proinflammatory oxidized lipids is the NADPH oxidase pathway (59,60).…”
Section: What Are the Mechanisms That Cause The Formation Of The Oxidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reactive species EPO and MPO form can also oxidatively modify host tissues. Under physiological conditions, both EPO and MPO use hydrogen peroxide (H 2 O 2 ) as one substrate and an assortment of co-substrates to generate an array of reactive oxidant species that can damage both proteins and lipids at sites of inflammation (7)(8)(9)(10)(11)(12)13). For example, we have shown that eosinophils use EPOgenerated oxidants to promote modification of lung and airway proteins during allergen challenge in mild asthma, and in severe asthma (9, 14 -16).…”
mentioning
confidence: 99%
“…In the presence of oxygen, these pyrrole adducts convert over time into highly stable lactam adducts, as well as hydroxylactam adducts ( 5,7 ). Increased concentrations of IsoK protein adducts have been observed in vivo during a wide variety of conditions associated with infl ammation and oxidative stress, including atherosclerosis, end stage kidney disease, myocardial infarction, Alzheimer's Disease, glaucoma, hyperoxia, allergic infl ammation, and experimental sepsis (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%